Pharmacokinetics and Toxicokinetics Roles of Membrane Transporters at Kidney Level - Jéssica Veiga-Matos; Fernando Remião; Ana Motales (Journal of Pharmacy & Pharmaceutical Sciences, 2020)
Transporters are large membrane proteins, which control the passage of various compounds through biological membranes. These proteins are divided into uptake and efflux transporters and play an important role in the toxicokinetics of many endobiotics and xenobiotics. The uptake transporters facilitate the absorption of these compounds from the blood into the proximal tubular cells, while the efflux transporters eliminate these compounds into tubular fluid (urine). Overall, the uptake is performed by the superfamily solute carrier (SLC) transporters, which are, mostly, located in the basolateral membrane. The organic anion transporters (OATs; SLC22), the organic cation transporters (OCTs; SLC22), the organic cation/carnitine transporters (OCTNs), and the organic anion transporting polypeptides (OATP; SLC21/SLCO) are some examples of uptake transporters of the SLC superfamily. On the other hand, the superfamily ATP-binding cassette (ABC) transporters carry out the elimination of the substances through the apical membrane of the proximal tubular cells. The multidrug resistance proteins 1 (MDR; ABCB), the multi resistance protein (MRP2; ABCC) and the breast cancer resistance protein (BCRP, ABCG) along with the multidrug and toxin extrusion (MATE), which is an SLC transporter, carry out the substance efflux of the cell, However, uptake transporters seem to be more efficient than efflux transporters, leading to an accumulation of compounds in proximal tubular cells and, consequently, to renal damage. The accumulation of compounds can also occur due to variations in the number of transporters that exist due to differences in sex, age, genetic polymorphisms and epigenetics. Furthermore, some substances can inhibit, induce or, eventually, activate these transporters, with consequent drug-drug interactions (DDIs) as a result of alterations on the toxicokinetics of xenobiotics, leading to an increase of their accumulation and, consequently, to renal damage. These compounds may be exogenous, such as antibiotics, antivirals, cisplatin, metals, herbicides, mycotoxins and drugs; or endogenous, like uric acid, bile acids, bilirubin conjugates and conjugated steroids. Thus, in this review, we will focus on the accumulation of exogenous compounds due to variations on renal transporters and the consequent biological effects caused by them.